The Effect Of Beauty Vloggers As Celebrity Endorser And Lifestyle Towards Purchase Decision Mediated By Purchase Intention (Study On Consumers Of Scarlett Brand Product In Bekasi Regency) - Ivani Khairunnisa; Taufiqurrahman Taufiqurrahman; Tengku Firli Musfar (Jurnal Impresi Indonesia, 2022)
This study aims to determine the effects of beauty vloggers as celebrity endorser and lifestyle to purchase decision through purchase intention. The population in this study is consumers of Scarlett brand product whose age 15-34 yeas old also domiciled in Bekasi Regency. Primary data was collected by questionnaire as an instrument to prove the results of the research, to test the hypothesis in this studyis using path analysis with Statistical Program for Social Science (SPSS) 20. The sampling method used a non-probability sampling method with a purposive sampling technique (125 people). The result shown that beauty vloggers as celebrity endorser and lifestyle partially have positive significant effect to purchase intention of Scarlett Brand Product, beauty vloggers as celebrity endorser has an effect but not significant positive to purchase decision of Scarlett Brand Product, lifestyle has positive and significant effect to purchase decision of Scarlett Brand Product, beauty vloggers and lifestyle partially effect to purchase decision through purchase intention of Scarlett Brand Product, and purchase intention has significant and positive effect to purchase decision of Scarlett Brand Product.